2018
DOI: 10.1088/1361-6463/aad7e5
|View full text |Cite
|
Sign up to set email alerts
|

Novel bifunctional Nd:YAG/Fe3O4 nanocomposite as nanothermometer/nanoheater for potential biomedical applications

Abstract: This work reports a novel bifunctional nanocomposite made of infrared-emitting nanophosphors and superparamagnetic nanoparticles, which simultaneously provides heating and temperature sensing at the nanoscale level. Highly luminescent Y3Al5O12:Nd3+ nanophosphors were synthesised by using a sol–gel route and were subsequently mixed with superparamagnetic nanoparticles producing a core–shell structure, which displayed superparamagnetic and fluorescent properties in the same nanostructured system. As a result, th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
4
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 36 publications
0
4
0
Order By: Relevance
“…4−6 At present, the optical/magnetic bifunctional materials reported in the literature are mainly composite materials, such as coating materials, mosaic materials, and so on. 7,8 Zhang et al reported the hollow Fe 3 O 4 @SiO 2 @α-NaYF 4 /Yb, Er composite, which can emit visible light under the excitation of near-infrared and has the effect of magnetic targeting under the action of an external magnetic field. 9 Abbas et al found that NaYF 4 :Yb, Er@Fe x O y modified the surface of the shell by a dopamine molecule, which makes the composite nanoparticles more water-soluble and less toxic.…”
Section: ■ Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…4−6 At present, the optical/magnetic bifunctional materials reported in the literature are mainly composite materials, such as coating materials, mosaic materials, and so on. 7,8 Zhang et al reported the hollow Fe 3 O 4 @SiO 2 @α-NaYF 4 /Yb, Er composite, which can emit visible light under the excitation of near-infrared and has the effect of magnetic targeting under the action of an external magnetic field. 9 Abbas et al found that NaYF 4 :Yb, Er@Fe x O y modified the surface of the shell by a dopamine molecule, which makes the composite nanoparticles more water-soluble and less toxic.…”
Section: ■ Introductionmentioning
confidence: 99%
“…Seeking ferromagnetic semiconductors with a high Curie temperature and inorganic luminescent materials (phosphors) with a short lifetime is a great challenge in semiconductor spintronics and projection television screen applications. Bifunctional materials, especially those with both photoluminescence (PL) and magnetism, are widely used in multifunctional devices and biological diagnosis and treatment due to their unique and superior properties. At present, the optical/magnetic bifunctional materials reported in the literature are mainly composite materials, such as coating materials, mosaic materials, and so on. , Zhang et al reported the hollow Fe 3 O 4 @SiO 2 @α-NaYF 4 /Yb, Er composite, which can emit visible light under the excitation of near-infrared and has the effect of magnetic targeting under the action of an external magnetic field . Abbas et al found that NaYF 4 :Yb, Er@Fe x O y modified the surface of the shell by a dopamine molecule, which makes the composite nanoparticles more water-soluble and less toxic .…”
Section: Introductionmentioning
confidence: 99%
“…31 Besides, Tejada et al worked with YAG: Nd/Fe 3 O 4 @SiO 2 nanocomposites that are excited at 813 nm that showed a thermal sensitivity of 0.14% K −1 . 32 Because PTT is not commonly performed with IONPs, these articles focus only on MNH. Recently, Ortgies et al proposed a poly-lactic-co-glycolic acid encapsulation of multicores (magnetite NPs and LaF 3 :Nd) for trifunction (MNH, PTT, and LNT) operations by showing a thermal sensitivity of 0.4% K −1 evaluated via multiparametric thermometry using two peaks (862.2 and 864 nm) after excitation at 808 nm.…”
Section: Introductionmentioning
confidence: 99%
“…Dong and Zink encapsulated magnetite NPs and NaYF 4 :Yb 3+ , Er 3+ nanorods in the silica matrix and excited at 980 nm (Yb 3+ ) . Besides, Tejada et al worked with YAG: Nd/Fe 3 O 4 @SiO 2 nanocomposites that are excited at 813 nm that showed a thermal sensitivity of 0.14% K –1 . Because PTT is not commonly performed with IONPs, these articles focus only on MNH.…”
Section: Introductionmentioning
confidence: 99%